ENGINEERING MODEL ON TRAFFIC VOLUME AT BOCIMI TOLL GATE - Syaiful, Syaiful; Maulani, Denia; Megawati, Dewi; Gibran, Reza; Wardhani, Asri Kusuma (Journal of Applied Engineering Science, 2025)
The Bocimi Toll Road, connecting Bogor, Ciawi, and Sukabumi, represents a critical infrastructure development in Indonesia, aimed at enhancing regional connectivity across West Java and Banten Provinces. Designed to facilitate access between satellite cities such as South Jakarta, Cianjur, and Rangkasbitung, the toll road is also anticipated to boost tourism in Bogor, Ciawi, and Sukabumi by improving accessibility. This study focuses on two primary objectives: analyzing traffic volume at key toll gates during peak hours and determining average travel times along the Bocimi Toll Road. The findings reveal that the Cigombong Toll Gate experiences high traffic volumes, predominantly from large trucks and heavy vehicles, necessitating the separation of heavy vehicle lanes to optimize traffic flow. Furthermore, the average travel time analysis indicates that the highest traffic flow, recorded at 703.04pcu/hour, occurs in the afternoon at Cigombong, while the lowest, at 506.26pcu/hour, occurs in the morning at the Ciawi Toll Gate. These results underscore the importance of targeted traffic management strategies to enhance the operational efficiency of the Bocimi Toll Road and support its role in regional economic and tourism development.